Investigation of simvastatin on micro and macro element levels in intestinal tissue for during early phase of sepsis - (:unkn) unknown (Academic Journals Inc., 2016)
Background: There are limited studies in the literature micro and macro elements of level during early phase of sepsis. The changes of micro and macro element levels plays important roles normal physiologic states and pathological states especially inflammation. Intestine is main organ for absorption of element. There are a lot of studies shown that simvastatin possess potent anti-inflammation and antioxidation capacity. But it is not clear simvastatin on element levels and its mechanism. Aim: This study aimed to observe the effect of prior treatment with simvastatin on elements in intestinal tissue of rats during the early-phase of sepsis. Methodology: Rats were divided into four groups: control, lipopolysaccharide (LPS) (20 mg kg−1, i.p.), simvastatin (20 mg kg−1, p.o.) and the simvastatin+LPS group. Selenium, zinc, iron, manganese, magnesium, calcium, sodium, copper and potassium element levels in intestinal tissue were analyzed by inductively coupled plasma-optical emission spectroscopy (icp-oes). This study measured serum and tissue levels of Tumor Necrosis Factor-α (TNF-α), interleukin-10 (IL-10) using ELISA. Serum and tissue TNF-α and IL-10 levels were higher in the simvastatin+LPS and LPS groups (p<0.05). The IL-10 levels was found higher in simvastatin+LPS group compared to LPS group (p<0.01). In the simvastatin+LPS group, levels of calcium and sodium were lower than those of LPS and controls (p<0.05 and p<0.01, respectively). Results: The levels of zinc, iron, potassium and copper were found increased in the simvastatin+LPS group compared with LPS group (p<0.05). The present study simvastatin have important effect on element metobolism especially zinc, copper, iron, potassium during sepsis. Conclusion: This study suggests that prior treatment with simvastatin may be effective in reducing tissue damage by increasing levels of zinc, copper, iron, potassium and IL-10 and decreasing levels of sodium and calcium in septic rats. © 2016 Hatice Yorulmaz et al.
Keywords: Elements; Intestine; Sepsis; Simvastatin